Answer:
The solution of the given system is (x,y) = (1,4)
Step-by-step explanation:
Here, the given system of equation is:
x = -3 + y
26 x - 5 y = 6
Now, substitute x = -3 + y in the second equation , we get
26 x - 5 y = 6 ⇒ 26 (-3 + y) - 5 y = 6
or, 26(-3) + 26(y) - 5y = 6
⇒ - 78 + 26 y - 5y = 6
⇒ 21 y = 84
⇒ y = 84 / 21 = 4 or , y = 4
So x = -3 + y = -3 + 4 = 1
Hence, the solution of the given system is (x,y) = (1,4)
Answer:
31° change
Step-by-step explanation:
If we want to find the change between two numbers, we need to imagine it like a number line.
<-------------0------------->
Let's plot -7 and 24 on this number line.
<----------
--0------------24>
If we want to get from -7 to 0, we increase by 7. To get from 0 to 24, we increase by 24.
So the total change is
.
Hope this helped!